Genome-wide oscillations in G + C density and sequence conservation - Moqtaderi, Zarmik; Brown, Susan; Bender, Welcome (Genome Research, 2021)
Eukaryotic genomes typically show a uniform G + C content among chromosomes, but on smaller scales, many species have a G + C density that fluctuates with a characteristic wavelength. This oscillation is evident in many insect species, with wavelengths ranging between 700 bp and 4 kb. Measures of evolutionary conservation oscillate in phase with G + C content, with conserved regions having higher G + C. Loci with large regulatory regions show more regular oscillations; coding sequences and heterochromatic regions show little or no oscillation. There is little oscillation in vertebrate genomes in regions with densely distributed mobile repetitive elements. However, species with few repeats show oscillation in both G + C density and sequence conservation. These oscillations may reflect optimal spacing of cis-regulatory elements.
10.1101/gr.274332.120